Parents’ Perspectives on the Need for Professional Development for Early Childhood Teachers in Botswana - Monyatsi , Kabita Bose Lois R Mberengwa Pedzani Perci (Nurture, 2012)
This study investigated parents’ perspectives regarding the necessity of a Professional Development programme for Early Childhood Development (ECD) teachers in Botswana. A quantitative survey research design was used. The sample size was 452 parents from various districts in Botswana. A questionnaire consisting of both closed and open-ended items was used to collect data which captured the parents’ views on a Professional Development programme for ECD teachers. The data were analyzed using SPSS Version 17 and presented using tables, graphs, cross-tabulations, chi-square test and binomial test and descriptive. The findings of the study show that the parents suggested a Professional Development programme for the ECD teachers that inculcates child care and communication skills, creation of appropriate teaching/learning environment, classroom management, professionalism, curriculum development and evaluation. The study recommended that clear policy is needed regarding basic qualifications and competencies of ECD teachers. A professional development programme which embraces all the key skills needed by ECD teachers is also recommended.